PENGUJIAN KEMBALI EFEK HARI SENIN DAN BULAN JANUARI DI BURSA EFEK INDONESIA - , RENSIE PARMAWATY ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research investigates the occurrence of Monday and Efek bulan Januariin Indonesia stock exchange. The data used in this research were secondary ones, both daily closing stock price and monthly ones within 2009-2012. There were 26 samples used, i.e. consistent stocks at the index LQ 45 during 2009-2012. In the testing, the samples were divided into eight subsamples: 2009, 2010, 2011, 2012, 2009-2010, 2010-2011, 2011-2012, and 2009-2012. The investigation was done by regression, with stock return as the dependent variable and dummy variable as the independent variable. The results of this study indicate that there are Efek hari Seninonly at a certain period, 2011, 2012, 201-2012, while for the other subsample did not happen. The results in Efek bulan Januarishowed that there was no Efek bulan Januariduring the observation period. If seen from the hypothetical testing, it shows that in April, the stock return was consistently higher than other months.